ANALISIS MARGIN PEMASARAN BERAS KECAMATAN SIBULUE KABUPATEN BONE - Muhdiar, Muhdiar; Halimah, Andi Sitti (Universitas Negeri Makassar, 2018)
This study aims was to determine the rice marketing channel, the magnitude of marketing margins earned any marketing agencies in each of the rice marketing channel at 3 villages in Subdistrict of Sibulue-Bone Regency, namely Kalibong, Polewali, and Massenrengpulu village. Respondent in research are farmers, traders, wholesalers and retailers. The results found that rice marketing in this area there are three forms of marketing distribution channel that is marketing channel I, farmer → consumer. Marketing channel II, farmers → wholesalers → retailers → consumer. Marketing channel III, farmers → wholesalers → consumers. In channel I does not have the amount of marketing margin because it does not go through intermediaries, on channel II the amount of margin earned by Rp.1.000 consists of margin traders of Rp.500, 00, retailers of Rp. 500.00. As for channel III the amount of margin obtained is Rp.500.00. So a profitable marketing channel that is channel I.